A Comparative Study of Protocols for Mouse Embryonic Stem Cell Culturing - Tamm, Christoffer; Pijuan Galitó, Sara; Annerén, Cecilia (PLOS ONE, 2013)
Most stem cell laboratories still rely on old culture methods to support the expansion and maintenance of mouse embryonic stem (ES) cells. These involve growing cells on mouse embryonic fibroblast feeder cells or on gelatin in media supplemented with fetal bovine serum and leukemia inhibitory factor (LIF). However, these techniques have several drawbacks including the need for feeder-cells and/or use of undefined media containing animal derived components. Culture of stem cells under undefined conditions can induce spontaneous differentiation and reduce reproducibility of experiments. In recent years several new ES cell culture protocols, using more well-defined conditions, have been published and we have compared the standard culture protocols with two of the newly described ones: 1) growing cells in semi-adherence in a medium containing two small molecule inhibitors (CHIR99021, PD0325901) and; 2) growing cells in a spheroid suspension culture in a defined medium containing LIF and bFGF. Two feeder-dependent mouse ES (mES) cell lines and two cell lines adapted to feeder-independent growth were used in the study. The overall aim has not only been to compare self-renewal and differentiation capacity, but also ease-of-use and cost efficiency. We show that mES cells when grown adherently proliferate much faster than when grown in suspension as free-floating spheres, independent of media used. Although all the tested culture protocols could maintain sustained pluripotency after prolonged culturing, our data confirm previous reports showing that the media containing two chemical inhibitors generate more pure stem cell cultures with negligible signs of spontaneous differentiation as compared to standard mES media. Furthermore, we show that this medium effectively rescues and cleans up cultures that have started to deteriorate, as well as allow for effective adaption of feeder-dependent mES cell lines to be maintained in feeder-free conditions.